Olive processing waste management : literature review and patent survey - Niaounakis, M. (Waste management series, 2006)
The book contains a comprehensive review of literature and patent survey concerning olive processing waste. Over 1,000 citations are presented. Wastes considered include olive cultivation solid waste, wastes arising from classical, three- and two-phase olive mills and wastes generated during table olive processing. In addition, information is presented concerning the management of spent olive oil (e.g. from cooking). The book is divided into five parts. Part I presents background information concerning the characterization of olive processing wastes, their environmental impacts if disposed untreated and the effect of utilised olive-mill technology on the quantity and quality of generated wastes. Part II presents physical, thermal, physico-chemical, biological and combined or miscellaneous processes for treating olive-mill wastes. Part III concerns information on utilization of such wastes with or without prior treatment. Part IV concentrates on table olive processing waste and presents information regarding its characterization, treatment and uses. Part V presents an economical and legislative overview regarding olive-mill waste. The book contains a bibliography, glossary of terms used in the text, subject, patent and author indices as well as pertinent internet sites and authorities. *Complete coverage of all available literature and patents concerning olive processing waste including economic and legislative issues *Critical review of up to date utilized processes concerning treatment and uses of such wastes *Determination of research needs for further utilization of such wastes.